2012
DOI: 10.1111/j.1740-0929.2012.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between villous height and the disaccharidase activity in the small intestine of piglets from nursing to growing

Abstract: Early weaning induces villous atrophy in the small intestine. Reduction in villous height in the small intestine after weaning is associated with reductions in brush-border enzyme activity. Body weight gain after weaning is, therefore, correlated with villous height. This evidence suggested that the maintenance of small intestinal structure and function after weaning is important for the growth of young pigs. On the other hand, the relationship between villous height and the activity of the digestive enzymes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…Marion et al () also reported that shortened small intestinal villus associates with absorptive capacity reductions. Our experimental result agreed with the previous report that brush border enzyme activity reduction in the small intestine relates to the reduction of VH (Hodin et al, ; Tsukahara et al, ). It may be possible that higher VH results in greater maltase, sucrase and ALP in the jejunum.…”
Section: Discussionsupporting
confidence: 94%
“…Marion et al () also reported that shortened small intestinal villus associates with absorptive capacity reductions. Our experimental result agreed with the previous report that brush border enzyme activity reduction in the small intestine relates to the reduction of VH (Hodin et al, ; Tsukahara et al, ). It may be possible that higher VH results in greater maltase, sucrase and ALP in the jejunum.…”
Section: Discussionsupporting
confidence: 94%
“…Early weaning induces villous atrophy and crypt hyperplasia in the small intestine, 33 and a reduction in villous height in the small intestine is associated with reductions in body weight gain after weaning. 34 Furthermore, there were alterations in electrolytes, and a lengthened crypt compartment in the jejunum in a rat lapatinib-induced diarrhoea model. 35 Compromising alterations in the villus–crypt structure are common in weaned pigs.…”
Section: Discussionmentioning
confidence: 96%
“…Tsukahara et al . () reported that the activities of maltase and sucrase were positively correlated with villus height in piglets. Vicente et al .…”
Section: Discussionmentioning
confidence: 97%
“…Until now, the mechanisms by which the higher activities of maltase and aminopeptidase obtained in rice feeding have been unknown and under consideration. Tsukahara et al (2013) reported that the activities of maltase and sucrase were positively correlated with villus height in piglets. Vicente et al (2009) have shown that villus area of the small intestine was larger in rice-fed pigs than in corn-fed pigs.…”
Section: Discussionmentioning
confidence: 99%